2016
DOI: 10.1016/j.amepre.2016.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity During the Early Years

Abstract: Context: Being physically active during the early years (age 0-6 years) is vital for healthy development. Identifying correlates and determinants of physical activity (PA) is crucial to guide effective interventions. This systematic review synthesized studies investigating potential correlates and determinants of PA during the early years, accounting for different types of PA assessment.Evidence acquisition: Nine electronic databases were searched from inception year (1900) until September 2014; data were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(68 citation statements)
references
References 158 publications
3
60
1
4
Order By: Relevance
“…Hence, reviews concluded that there was insufficient evidence to draw conclusions regarding correlates of SB in young children [17, 50]. On the other hand, consistent correlates of preschool children’s PA identified in reviews exist [1416]. These include gender (male preschoolers are more active than female preschoolers), parental PA (parent’s PA is positively associated with their child’s PA), parents’ participation in children’s PA (children of parents who actively engage in PA with their children are more active than children of parents who do not participate), time outdoors (outdoor play time is positively associated with PA) and gross motor skills (MVPA is positively associated with gross motor skills).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, reviews concluded that there was insufficient evidence to draw conclusions regarding correlates of SB in young children [17, 50]. On the other hand, consistent correlates of preschool children’s PA identified in reviews exist [1416]. These include gender (male preschoolers are more active than female preschoolers), parental PA (parent’s PA is positively associated with their child’s PA), parents’ participation in children’s PA (children of parents who actively engage in PA with their children are more active than children of parents who do not participate), time outdoors (outdoor play time is positively associated with PA) and gross motor skills (MVPA is positively associated with gross motor skills).…”
Section: Discussionmentioning
confidence: 99%
“…While in late childhood and adolescence the decline in PA with age is a common finding, this trend is less evident in younger children [23]. Several reviews have reported no age effect in the preschool population [14, 16, 51]. In this study, we found that older preschool-aged children were more physically active than younger ones; both TPA and MVPA were positively associated with age and increased by an average of 10% and 16%, respectively, per year (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent review by Bingham and colleagues [20], included an additional five studies that investigated paternal influences on children’s physical activity separately to maternal influences. Taylor and colleagues, in their longitudinal study of 244 pre-school children and their parents, reported that parental activity (mothers and fathers) was weakly positively correlated with the activity of their three and four-year-old children.…”
Section: Introductionmentioning
confidence: 99%